Maritime Axis And Indonesia’s National Security: Challenge And Hope - Ridwan, Safril Hidayat dan (Indonesia Defense University, 2017)
Abstract - The maritime and marine potentials are so great on the one hand, were a blessing on Indonesia's geographical condition, but on the other hand, it can lead to conflict. Exploitation and illegal activities on marine resources without considering to sustainability will worsen the welfare of society and oftenly conflicting international relations. As a country that becomes the crossing of foreign ships where four straits of the seven important straits of the world exist in Indonesian waters, Indonesia is a country that is vulnerable from the side of maritime security. Crime in Indonesian waters is still frequent, either by Indonesian citizens themselves or foreign nationals. The Government of Indonesia with the Nawa Cita program has the vision of Indonesia as a maritime axis of the world. Meanwhile, as a policy, the successful implementation of maritime axis policy is largely determined by content of policy and context of implementation. The successful implementation of maritime axis policy will impact the realization of the welfare and security of Indonesian society. This article uses a qualitative approach with data sources and literature related to maritime axis. Validity and reliability of data is done by reference triangulation. The results show that the implementation of maritime shaft policy still requires the readiness of the implementer as the front guard of maritime axis policy along with the development of maritime infrastructure of international standard.Key words: maritime axis, content of policy, context of implementation, national security